Circulating endothelial microparticles and miR-92a in acute myocardial infarction. Issue 2 (27th March 2017) - Zhang, Yuchen; Cheng, Junjun; Chen, Fang; Wu, Changyan; Zhang, Junmeng; Ren, Xuejun; Pan, Yu; Nie, Bin; Li, Quan; Li, Yu
Abstract : Microparticles (MPs) and miRNAs have been shown to play important roles in coronary artery disease (CAD) by monitoring endothelial dysfunction. The present study aims to investigate the diagnostic value of endothelial MPs (EMPs) and miRNAs ( miR-92a or miR-23a ) as biomarkers in distinguishing patients with acute myocardial infarction (AMI) from those with CAD. Plasma samples from 37 patients with AMI, 42 patients with stable CAD (SCAD), and 35 healthy adults were collected for investigation in the present study. The numbers of CD31+/CD42b− MPs, CD31+/CD42b+ MPs, and CD31−/CD42b− MPs were measured by flow cytometry and the levels of miR-92a and miR-23a were analyzed using reverse transcription-quantitative PCR. Moreover, cardiac troponin I (cTnI) expression was detected by ELISA to serve as a routine diagnostic parameter. The number of CD31+/CD42b− was higher in AMI group than those in SCAD and healthy groups. Besides, the expression of miR-92a was higher in AMI group compared with two other groups. Furthermore, evidence showed that there was a positive correlation between the levels of CD31+/CD42b− MPs and miR-92a . Finally, the receiver operating characteristic (ROC) curve revealed that the area value under the curve of CD31+/CD42b− MPs, miR-92a and cTnI was 0.893, 0.888, and 0.912 respectively. CD31+/CD42b− MPs and miR-92a might have great potential to provide diagnostic value for AMI and could probably regulate the endothelial dysfunction in AMI patients.